Sustainable construction pro an optimistic world scenario - Koukkari, Heli (2009)
Building and civil engineering has greatly contributed to shaping and structuring the world as we know it nowadays. It has paved ways to industries and contributed to function of societies. Before born of engineering as a vocation or discipline, the practical workmanship had produced prominent buildings and artifacts throughout centuries. The built environment has evolved to frame nearly all human activities. Parallel, the production and use of built environment has grown more and more harmful to the nature. In the circumstances of global threats, building and civil engineering has giant tasks but also magnificent opportunities. The big challenge of building and civil engineers is now to work for an optimistic world scenario by developing technologies and processes of sustainable construction. The hard core of sustainable construction needs new environmentally friendly products and technologies. The soft dimensions of sustainability need knowledge on traditions and cultures. The design methods and business models promoting sustainability ensure that the potential of “green promise” is utilized. To put things happen, new pioneers are needed. Knowing about past and learning about foresights give valuable guidance for work and life.